Methodology of conducting public consultations in the CONCISE project - Brzeziński, Kamil (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
The public consultations carried out under the CONCISE project are an example of the unprecedented activity in Poland. No similar project – using the World Wide Views methodology and involving one hundred participants from different parts of the country, with different socio-demographic characteristics – has been carried out in Poland so far. The uniqueness of this initiative was related to, among other things, the enormous amount of work, and in particular, the development of a methodology that would guarantee the success of the entire project. This chapter aims to present the research process: its methodology, including the identification of particularly problematic elements that appeared during the project implementation – experiences and problems that were encountered during the implementation of the research, as well as ways of dealing with them. Researchers who choose to conduct participatory research face a significant challenge. In this context, presenting this project “from the inside” will help other researchers and scientists implement similar projects.